2012
DOI: 10.1111/j.1540-5826.2012.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐Based Strategies for Improving the Reading Comprehension of Secondary Students: Implications for Students with Learning Disabilities

Abstract: Reading comprehension is a complex skill that places significant demands on students, beginning with elementary school and continuing through the secondary grades. In this article, we provide an overview of possible factors associated with problems in reading comprehension among secondary students with learning disabilities. Discussion underscores the fact that comprehension problems are evidenced by a heterogeneous group of students. We argue that it is important for teachers to align an intervention with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 124 publications
(337 reference statements)
2
30
0
5
Order By: Relevance
“…The third implication from this study is that, through the use of technology, specifically CBGOs, students may be better able to increase vocabulary knowledge which ultimately better prepares students with disabilities for their post-transition goals (Kim et al, 2017;Vaughn et al, 2015;Watson et al, 2012). Overall, in these ways, results from this study positively supports that further evidence exists regarding the effectiveness of computerized graphic organizers helps to increase vocabulary acquisition of students with high-incidence disabilities.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The third implication from this study is that, through the use of technology, specifically CBGOs, students may be better able to increase vocabulary knowledge which ultimately better prepares students with disabilities for their post-transition goals (Kim et al, 2017;Vaughn et al, 2015;Watson et al, 2012). Overall, in these ways, results from this study positively supports that further evidence exists regarding the effectiveness of computerized graphic organizers helps to increase vocabulary acquisition of students with high-incidence disabilities.…”
Section: Discussionsupporting
confidence: 52%
“…With the emphasis of rigor in education and, thus, the cognitive demand placed upon students steadily increasing, the challenge placed before students is accumulating (Kim et al, 2017;Lombardi et al, 2017;Malcolm & Roll, 2017;Vaughn et al, 2015). To this end, teaching vocabulary is not only vital, but is a key component in the success of students with disabilities at the secondary level (Vaughn et al, 2015;Malcolm & Roll, 2017;Watson et al, 2012). The use of technology to teach vocabulary through an evidence-based approach such as graphic organizers makes pedagogical sense, and is a need within the educational community, but needs to be researched to determine its effectiveness; therein lies the basis for this study.…”
Section: Background Of the Studymentioning
confidence: 99%
“…D'ailleurs, au secondaire, les exigences en matière de compréhension qu'imposent les textes disciplinaires sont fréquemment plus élevées que les compétences des élèves (Shanahan & Shanahan, 2008). Ainsi, tout au long du primaire, pour réussir leur scolarité, les élèves ont besoin de développer leur vocabulaire, d'être exposés à des textes de complexités variables sur une grande diversité de sujets venant de plusieurs sources, en plus de développer des stratégies de compréhension de lecture à travers toutes les disciplines (Biancarosa & Snow, 2004;Torgesen, Houston, Rissman, Decker, Roberts & al., 2007;Watson, Gable, Gear & Hughes, 2012).…”
Section: Problématiqueunclassified
“…Therefore, it is suggested that paraphrasing should be taught to students before or during summarization (Watson et al, 2012). Reading skills researchers define the paraphrasing as a successful comprehension strategy that combines questioning, understanding, and summarizing skills (Schumaker, Denton & Deschler, 1984citied Katims & Harris, 1997.…”
Section: Teaching Rap Paraphrasing Strategy For Frustration-level Reamentioning
confidence: 99%
“…Identifying the main idea and details of a text is an essential ability for successful reading comprehension and is generally considered a prerequisite for higher-level strategies (Watson, Gable, Gear & Hughes, 2012).…”
Section: Introductionmentioning
confidence: 99%